2019
DOI: 10.4236/fns.2019.1011093
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Utilization of Mushroom as a Food Supplement among Families in Selected Local Government Areas of Cross River State, Nigeria

Abstract: The demand for health consciousness to prevent malnutrition, a high risk factor in developing countries especially in the rural areas is increasing. This study was designed to assess the level of knowledge and utilization of mushroom as a food supplement in six Local Government Areas of Cross River State, one predominantly urban and the other five mostly rural. Data were collected using a structured questionnaire from a total of 250 participants. Findings revealed that 178 (71.2%) of respondents had good knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The respondents were interviewed one-on-one. The semi-structured questionnaire was used in the current study and was adapted from earlier surveys (Mgbekem et al, 2019;Alduhisa & Demayo, 2019) with a few minor adjustments. The local vernacular was used to translate the English questionnaire.…”
Section: Survey and Interviewmentioning
confidence: 99%
“…The respondents were interviewed one-on-one. The semi-structured questionnaire was used in the current study and was adapted from earlier surveys (Mgbekem et al, 2019;Alduhisa & Demayo, 2019) with a few minor adjustments. The local vernacular was used to translate the English questionnaire.…”
Section: Survey and Interviewmentioning
confidence: 99%
“…There is a study which found communities that abstain from harvesting forest mushrooms due to insufficient knowledge in identifying edible mushrooms [20]. Therefore, knowledge plays an important role in the utilization of forest mushrooms [12,13].…”
Section: Level Of Formal Educationmentioning
confidence: 99%
“…Due to their experience, they are certain to have sufficient knowledge regarding the types of edible mushrooms. This knowledge is an important asset for a mushroom hunter to have [11][12][13][14]20,24]. Regarding the role of experience in a business, [25] stated that ample experience in business activities will allow a person to identify problems obstacles that occurred.…”
Section: Experience In Mushroom Huntingmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from a structured questionnaire assessing mushroom utilization by 250 study participants in Nigeria show that 82% of the respondents utilize mushrooms as a food supplement [10]. These mushrooms are the most cost-effective source of a healthier diet tackling food insecurity, diversification and malnutrition for the families in this region of the country.…”
Section: Contemporary Usage Of Edible Wild Mushrooms -Ethnomycological Aspectsmentioning
confidence: 99%